Fundamentals of Determining the Stressed State of Semi-Elastic Space under the Action of a Force Applied to One Point When Solving Contact Problems (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article presents the definition of the stressed state of a semi-elastic space under the action of a force applied to one point, and also presents methods for determining the components of the stress tensor and the components of the strain tensor.